Perilaku Utang Dan Piutang Pengusaha UMKM Penerima Penjaminan Kredit Dari Bank ONP - Laurensius, Michael (Cendekia Niaga, 2022)
MSME entrepreneurs contribute greatly to the GDP of the Indonesian economy, so whether if crisis occurs, government intervention is necessary to accelerate recovery, one of which is credit guarantees policy. This study aims to examine the effect of credit guarantee intervention policies on MSME banking lending and its impact on MSME trade payables and accounts receivable. The research was conducted using a descriptive causal method to explain the relationship between credit guarantees, banking credit, and trade payables and trade receivables of MSMEs. The results of the study explain that there is a significant effect of providing credit guarantees on the amount of bank credit for MSME entrepreneurs, then from the amount of banking credit disburse it is known that there is no significant effect on the behavior of trade payables and there is a significant effect on trade receivables. In addition, this study also sees that in the implementation of the provision of credit guarantees that there is an adverse selection and moral hazard carried out by PT Jamkrindo as the guarantee provider and MSME entrepreneurs as the beneficiaries of the guarantee.